2014
DOI: 10.1007/s00204-014-1386-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and its oligomers: modulation of sphingolipid metabolism and signaling in disease

Abstract: Resveratrol, a natural compound endowed with multiple health-promoting effects, has received much attention given its potential for the treatment of cardiovascular, inflammatory, neurodegenerative, metabolic and age-related diseases. However, the translational potential of resveratrol has been limited by its specificity, poor bioavailability and uncertain toxicity. In recent years, there has been an accumulation of evidence demonstrating that resveratrol modulates sphingolipid metabolism. Moreover, resveratrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 203 publications
(237 reference statements)
2
10
0
Order By: Relevance
“…Oligomers with more repeating resveratrol units were more active than smaller oligomers, as evidenced by the order of their potency: Trimers (cis-and trans-gnetin H, suffruticosol A-C, cis-and trans-suffruticosol D), followed by dimers (cis-and trans-ε-viniferin) and, lastly, the resveratrol monomer. This observation is consistent with previous findings of the structure-antioxidant activity of resveratrol oligomers (30,31). Secondly, the double bond in the stilbenic skeleton and its trans-isomerism were important to the antitumor activity of oligostilbenes.…”
Section: Discussionsupporting
confidence: 92%
“…Oligomers with more repeating resveratrol units were more active than smaller oligomers, as evidenced by the order of their potency: Trimers (cis-and trans-gnetin H, suffruticosol A-C, cis-and trans-suffruticosol D), followed by dimers (cis-and trans-ε-viniferin) and, lastly, the resveratrol monomer. This observation is consistent with previous findings of the structure-antioxidant activity of resveratrol oligomers (30,31). Secondly, the double bond in the stilbenic skeleton and its trans-isomerism were important to the antitumor activity of oligostilbenes.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that the EC 50 of three cis isomers were significantly higher than their corresponding trans isomer, which agreed with our current knowledge that the trans isomer of natural compounds is a more active form than cis because of its lower steric hindrance [22]. The activity of oligostilbenes to promote chondrocyte proliferation often increased with the degree of polymerization, which was consistent with their structure-antioxidant activity [23,24]. Additionally, both of cis-suffruticosol D and cis-gnetin H are trimers that differ only in their three-dimensional structures but had significant differences in their efficacies, which indicated that the effect of three-dimensional structure is also worth paying attention.…”
Section: Discussionsupporting
confidence: 91%
“…In addition some evidences demonstrate that resveratrol modulates sphingolipid metabolism by forming higher order oligomers that exhibit better selectivity and potency in modulating sphingolipid metabolism. 38 It has been determined, that resveratrol has very low bioavailability and is rapidly metabolized to yield plasma and tissue levels that are several-fold lower than those typically used in experiments with cultured cells. On Fig.…”
Section: In Foodsmentioning
confidence: 99%